EFEKTIVITAS PENGGUNAAN GYMBALL TERHADAP NYERI PUNGGUNG BAWAH PADA IBU HAMIL - Rauda, Rauda; Erni Naibaho; Novy Ramini Harahap; Agustina Indah Wati Simatupang (Sekolah Tinggi Ilmu Kesehatan Bakti Utama Pati, 2025)
Low back pain during pregnancy is a common complaint experienced by most pregnant women, particularly in the second and third trimesters. This pain can cause discomfort and lead to psychological effects such as fear, anxiety, and stress. One alternative method used to alleviate low back pain in pregnant women is the use of a gymball Objective:To determine the effectiveness of gymball exercise in reducing low back pain in pregnant women. Methods:mThis study used a quasi-experimental design with a one-group pretest-posttest design. The population consisted of 48 pregnant women. Sampling was conducted using purposive sampling based on specific inclusion criteria. The gymball intervention was carried out for seven consecutive days. Results: The study showed that before the intervention, the majority of participants (86.7%) experienced moderate low back pain. After the gymball exercise, the majority (86.7%) reported mild pain. The statistical analysis yielded a p-value of 0.000, which is less than ? = 0.05, indicating that the hypothesis was accepted—there is a significant effect of gymball exercise in reducing low back pain in pregnant women at the Hanna Kasih Primary Clinic in Medan. Conclusion:The study concludes that gymball exercise is an effective alternative intervention for reducing low back pain in pregnant women.